Effective countering new terrorism : a Singapore case study. - Julie S. Seckel. (2008)
The center of gravity in the war on terror is the Muslim community at-large as opposed to the leadership cadre of a particular terrorist group. Therefore, an effective terrorism countermeasures program is comprehensive, comprised of both direct and indirect methods. Traditional security is no longer adequate to protect nations against today's virulent enemy. Singapore's leadership recognizes the Muslim community as the center of gravity as evidenced by the current comprehensive terrorism countermeasures strategy.